Ethcinity And Integration Of Multicultural Society In Makassar City - Kasmita, Maya; Wardah, Siti Syarifah Wafiqah; Seppa, Yusi Irensi; Rachmatan, Rachmatan; Armansyah, Budi (Pinisi Business Administration Review, 2024)
Qualitative Research. The subject of this research is Makassar City, looking at ethnicity and integration in the multicultural society ofMakassar City. The aim of this study to analyze the relationship between ethnicity and integration in a multicultural society whileanalyzing the impact of integration on harmony and stability in the context of a multi-ethnic society. This research can help understandthe dynamics and interactions between ethnic groups in this city and their impact on identity formation and integration as well as provide insight to the community to better understand ethnic diversity and strengthen community involvement in building an inclusive and sustainable society. The data collection method is through interviews and using an interactive model. Keywords : etnisitas, integrasi, multikultural